The Training of Digital Media Utilization in English Online Learning for Students and Alumni in Pontianak - Ana Fergina; Stella Prancisca; Nining Ismiyani; Suparjan Suparjan; Yusawinur Barella; Andini Linarsih (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2021)
The need for technology progresses along with the widespread use of science and technology in various fields, especially in education, which is perceived as a solid foundation for the nation's progress. Increasingly tighter global competition also demands every government and country innovate and improve its nation's quality. Therefore, as educational instruments, educators always strive to create a quality education system for Indonesia's better future. Efforts to improve the quality of education in teaching English by adapting to technological advances can be one of the lights for this nation's future, especially in a global pandemic this year. For this reason, the authors initiated the training on the utilization of digital media in online English learning classes for students and alumni in Pontianak. It aims to positively and significantly impact online learning quality for students and alumni of universities in West Kalimantan. This Community Service was conducted by six English lecturers and one RELO trainer from New York, United States. It was held in three stages from July to November 2020. The first stage was training for teacher volunteers who were also graduates from three universities in Pontianak. This stage was carried out online and guided by a representative from the United States RELO, Yuta Otake. In the second stage, the teacher volunteers practiced teaching six classes at a partner school, SMA Santun Untan. The last step was the Virtual English Academic Camp, where students were invited to take part in exciting online academic activities and gameshows for three days. This Community Service has succeeded in providing adequate digital media utilization training in online English learning class to enhance understanding and English language skills for students and alumni of universities in Pontianak. In addition, this activity also presented positive impacts on the development of skills and motivation in learning foreign languages for the students of SMA Santun Untan